SISTEM INFORMASI PENGELOLAAN ASET (Studi Kasus: PPSDM MIGAS Cepu) - Joko Handoyo (Sekolah Tinggi Teknologi Ronggolawe Cepu, 2017)
Asset Management Information System is an integrated totality consisting of processing equipment including collectors, procedures, processingpersonnel and software. Asset Manager is an important subject in an organization. Humans have the ability to move all organizational resources.Without a good asset manager, the organization will be difficult to develop because the strength of every organization lies in the employeewho manages and handles it. In improving the asset management system in PPSDM MIGAS Cepu with emphasis on information system,required a system that is relatively fast, precise and accurate. To avoid inefficiencies, inefficiencies and to improve asset managementperformance in maintaining and managing assets in the relatively large and large number of MIGAS PPSDM Cepu and scattered in severalplaces in Cepu. By using the approach through several stages to analyze and design the system, the process is developed through the use of acycle of activity analyzer and user in a specific (structured), the method SDLC (System Development Life Cycle) with waterfall model. In thissystem for programming using PHP (PHP : Hypertext Prepocessor) and MySQL (My Structured Query Language) programming language byusing CodeIgniter. This information system consists of components of asset registration, classifying the type of asset according to the standardasset code, assigning the asset responsible, establishing the condition of the asset and later depreciating the asset value so that the asset can bemanaged properly, deleted if the condition is damaged, and the removal from the list assets of PPSDM Migas Cepu.